(untitled) (AYUSHDHARA, 2020)
Medoroga is a condition in which there is an excessive accumulation of Meda Dhatu in the body. Accumulation of Medo Dhatu in different parts of the body causes blockage of Strotsa which ultimately leads to poor nourishment of other Dhathus. Lack of exercises and Kaphavardhak Ahar Viharar are the two main causes of Medoroga. In modern times, way of life has changed drastically to quick nourishments and inactive tendencies throughout the world. Because of these factors, accumulation of Meda dhatu happens immensely. In Ayurveda, dyslipidemia is considered under Medoroga. Dyslipidemia is an emerging serious health abnormality associated with co-morbidities including CVD that continues to be the leading cause of death worldwide. It is characterized by an increase in cholesterol, triglycerides, LDL levels, and a decrease in HDL levels. The present study has been designed to compare the efficacy of Triphala Kwath and Trikatu capsules on various clinical parameters in the management of Medoroga w.s.r to dyslipidemia. Twenty patients fulfilling the inclusion criteria were randomly selected for the trial and put into two groups of ten patients each. Trikatu capsules were given to patients in group I and Triphla kwath with Madhu and Trikatu capsules in combination were given to patients of group II for 8 weeks. Patients were thoroughly assessed on various scientific parameters during the complete trial period. In group II, a significant (p<0.001) improvement was observed in subjective parameters and serum cholesterol, triglycerides, LDL, VLDL levels while in group I, a significant (p<0.001) improvement was observed in HDL only. It may affirmatively be construed from the study that the best impact of the trial drugs was observed with Triphala Kwatha with Madhu and Trikatu Capsule together (i.e. Group II). This combination therapy was most effective in reducing the overall lipid profile with substantial gains related to subjective as well as objective parameters without any adverse effects.